2013
DOI: 10.1186/2051-1426-1-s1-p225
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside containing nano-proteoliposome dampens myeloid-derived suppressor cells function and ability to cross-present tumor antigens: a new approach to recover CTL function on tumor bearing individuals

Abstract: Cite this article as: Fernández et al.: Ganglioside containing nanoproteoliposome dampens myeloid-derived suppressor cells function and ability to cross-present tumor antigens: a new approach to recover CTL function on tumor bearing individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…VSSP were proved to modulate the suppressive activity of tumor-derived MDSCs in mice by inducing their differentiation to APCs (Fernández et al 2011(Fernández et al , 2013, and on the basis of these results, the development of a vaccine able to target these immunosuppressive cells whilst eliciting an immune response towards the associated antigen has been proposed.…”
Section: Nanocarriers Targeted To Mdscsmentioning
confidence: 99%
“…VSSP were proved to modulate the suppressive activity of tumor-derived MDSCs in mice by inducing their differentiation to APCs (Fernández et al 2011(Fernández et al , 2013, and on the basis of these results, the development of a vaccine able to target these immunosuppressive cells whilst eliciting an immune response towards the associated antigen has been proposed.…”
Section: Nanocarriers Targeted To Mdscsmentioning
confidence: 99%
“…Nevertheless, these splenic myeloid cells did not exert any relevant immunosuppression on T cells. In addition, the injection of this adjuvant in tumour-bearing mice was able to modulate the phenotype of splenic MDSC towards APCs and strongly reduce their ability to impair cytotoxic T cell activation (182,186). A similar example was provided by Thomas et al, who showed that poloxamer-stabilized poly (propylene sulfide) nanoparticles (30 nm), loaded with either CpG or paclitaxel, were able to specifically target tumour-draining lymph nodes and reduce MDSC activity (187) ( Table 3).…”
Section: Therapeutic Interventions On Mdscmentioning
confidence: 99%
“…Nanomedicine combined with immunotherapy aimed at inhibiting immune cell activation or recruitment via an appropriate drug delivery platform might represent a potent intervention approach to fight diseases [ 20 , 21 ]. For instance, nanoproteoliposomes were deployed as nanocarriers for the antigen GM3 ganglioside in renal carcinoma-bearing mice, demonstrating that these nanoproteoliposomes could significantly transform the splenic DC phenotype towards APCs, followed by inhibition of the immune-suppressive characteristics of splenic DCs to promote subsequent cytotoxic T-cell activation [ 22 , 23 ]. Moreover, polymeric nanoparticles loaded with CpG or paclitaxel were found to effectively target DCs within lymph nodes, which drastically reduced DC immune activity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%